Long survival in acute myelogenous leukaemia: an international collaborative study. Issue 6265 (28th February 1981) - Whittaker, J A; Reizenstein, P; Callender, S T; Cornwell, G G; Delamore, I W; Gale, R P; Gobbi, M; Jacobs, P; Lantz, B; Maiolo, A T; Rees, J K; Van Slyck, E J; et al.
Abstract : A group of 82 adult patients with acute myelogenous leukaemia had survived in continuous first remission for more than three years was studied. These long-surviving patients were being treated at 12 referral centres in Europe and the USA, and they were compared with other patients with acute myelogenous leukaemia from 10 of these centres. There was no clear difference in the amount of induction chemotherapy or the time taken to achieve remission. Immunotherapy was not found to improve chances of long-term survival. The 82 patients were also compared with a group of 115 patients who had no appreciable difference in the number of blood or marrow myeloblasts between these two groups at presentation, but the long survivors had significantly higher initial platelet counts and were slightly younger. The long survivors also tended to have a lower total white cell count at presentation and lower granulocyte counts; there was no obvious explanation for these differences. Eight of the 82 patients relapsed from three to four years after remission and two (of 69 patients) after four to five year. Thereafter relapse was rare, and it seems likely that some of the 40 patients who have survived for five years or more are cured.